The Aplication of The “Skunda’s Model” in The Creation of The Environmentally Behavior - skunda diliarosta (Pelita Eksakta, 2019)
Vegetable farmers in the city of Payakumbuh still use a lot of pesticides and chemical fertilizers in controlling disease pests and increasing vegetable productivity. The solution that can be given to overcome these problems are by increasing farmers' knowledge about the impact of the use of chemicals on health and the environment and the importance of environmentally sound behavior in farming activities through the application of the Skunda's Message model. This Model is a behavior formation model that is obtained from the combined results of several theories of behavior and needs in the field. The method used in the application of the Skunda's Pesankan model is to conduct workshops on the Importance of Environmental Insight Behavior in Farming Activities, video playback on the Impact of the Use of Chemicals in Farming Activities on the Environment and Health, and a module on Utilizing Natural Materials in Pest and Disease Eradication and Fertilization Activities Vegetable. The results of these activities showed an increase in people's knowledge and enthusiasm for farming without using chemicals. This is evident from the emergence of strong motivation and desire from vegetable farmers to immediately carry out agricultural activities that are free of chemicals. Thus, the application of the Skunda's Pesankan model can increase vegetable farmers' knowledge of environmentally sound behavior in vegetable farming activities in Payakumbuh City.